How to train a cowboy - Carson, Caro (Carson, Caro. Texas rescue., 2016)
Though Marine hero Benjamin Graham doesn't know the first thing about ranching, his new job is the lifeline he desperately needs. Without the help of feisty cowgirl Emily Davis, though, he's lost--in more ways than one. But as their attraction turns combustible, the hardened battle vet turns away from the gorgeous college coed. She might know every inch of her family's homestead, but Graham doesn't want her to know his pain. Though Marine hero Benjamin Graham doesn't know the first thing about ranching, his new job is the lifeline he desperately needs. Without the help of feisty cowgirl Emily Davis, though, he's lost--in more ways than one. But as their attraction turns combustible, the hardened battle vet turns away from the gorgeous college coed. She might know every inch of her family's homestead, but Graham doesn't want her to know his pain"--Pg.4 of cover.